Case Report: Vitreous Amyloidosis Caused by a TTR Lys55Asn Mutation With Intraoperative Suprachoroidal Hemorrhage - Xu, Qing; Wang, Xinting; Zhang, Zhengpei; Li, Jie; Liu, Haiyang; Ji, Sujuan; Qiao, Lei; Gong, Chaoju; Feng, Ruifang; Li, Suyan (Frontiers in Medicine, 2022)
We report a vitreous amyloidosis patient with white vitreous opacities (footplates) adhering to the posterior lens capsule. A positive Congo-red stain and transthyretin (TTR) Lys55Asn mutation confirmed the diagnosis of vitreous amyloidosis. Optical coherence tomography (OCT) revealed fern-like material adhering to the the posterior pole retinal surface in both eyes. Visual acuity significantly improved after the first vitrectomy, but vitreous opacities recurred 4 years later. The patient appeared to have aggravated sensorimotor neuropathy and severe autonomic dysfunction at the same time. He developed intraoperative suprachoroidal hemorrhage during the second vitrectomy.